Report of an outbreak of Clostridium difficile infection caused by ribotype 053 in a neurosurgery unit. Issue 3 (May 2015) - Nagar, Aaron; Yew, Peter; Fairley, Derek; Hanrahan, Mary; Cooke, Stephen; Thompson, Irene; Elbaz, Wesam
Background: We describe an outbreak of Clostridium difficile infection (CDI) with ribotype 053, a possible hypervirulent strain that causes outbreaks, in a neurosurgical unit. Outbreak investigation: The outbreak was investigated by creating a timeline of all toxin positive patients with root cause analysis, supplemented with ribotyping results, hand hygiene and environmental audits. There were five cases of CDI, three caused by ribotype 053 indicating transmission. Infection prevention measures: These included a short period of ward closure to allow enhanced cleaning, including use of vaporised hydrogen peroxide, isolation of infected patients, reinforcement of hand hygiene, education of all staff on C. difficile, reduction of shared bay occupancy from six to four, and addressing staffing levels. Discussion: The patients with ribotype 053 all had long inpatient stays and had required several courses of broad-spectrum antibiotics for aspiration pneumonia. They also required enteral feeding, which can cause diarrhoea, and during long inpatient stays they had multiple toxin negative faecal samples making clinical diagnosis of CDI difficult. Hence they were not isolated promptly, leading to transmission. This is the first reported outbreak of C. difficile ribotype 053 in the UK and highlights the unique aspects of an outbreak in neurosurgical patients.